Virtual teaching during the COVID-19 pandemic. Issue 5 (May 2021) - Masterton, Gary; Zargaran, Alexander; Zargaran, David
Abstract : Disruption of services has resulted in a profound knock-on effect for plastic surgery trainees, with limited training opportunities available. The emergence and increased engagement with novel surgical technologies including Augmented and Virtual reality simulation represents an essential adjunct to mitigate limited training opportunities, though is in itself necessary but not sufficient for plastic surgery training. "Hands-on" experience remains important, but simulation may help to bridge the important gap between theory and practice. With the likely future pervasive nature of technology in training, important consideration must be given to both security and consent, which should be at the forefront of developers minds at the earliest possible stage.